2022
DOI: 10.1186/s12935-022-02467-4
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis identifies LMNB1 as a target to redress Th1/Th2 imbalance and enhance PARP inhibitor response in human cancers

Abstract: Background Emerging evidence suggests that LMNB1 is involved in the development of multiple cancer types. However, there is no study reporting the potential role of LMNB1 in a systematic pan-cancer manner. Methods The gene expression level and potential oncogenic roles of LMNB1 in The Cancer Genome Atlas (TCGA) database were analyzed with Tumor Immune Estimation Resource version 2 (TIMER2.0), Gene Expression Profiling Interactive Analysis version 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Normally, the Th1/Th2 ratio is in equilibrium. It was shown that cytokines released by Th2 cells and Th2 are elevated in various human cancers ( 36 ) and patients with a Th2-dominant response have a worse prognosis than patients with Th1/Th2 balance ( 37 , 38 ). We also found that in LIHC, THCA, KIRP, and KIRC, the KIFscore was positively correlated with Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…Normally, the Th1/Th2 ratio is in equilibrium. It was shown that cytokines released by Th2 cells and Th2 are elevated in various human cancers ( 36 ) and patients with a Th2-dominant response have a worse prognosis than patients with Th1/Th2 balance ( 37 , 38 ). We also found that in LIHC, THCA, KIRP, and KIRC, the KIFscore was positively correlated with Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interaction analysis with of CYP4A22 polymorphisms with covariate (age, gender, smoking and drinking) was performed using SNPStats. Using the SangerBox database to visualize the significant results of the stratified analysis and the forest map was drawn ( https://www.snpstats.net/start.htm?q=snpstats/start.htm ) [ 17 ]. In addition, since multiple hypothesis tests may increase the false positive probability, we used FPRP (false-positive report probability) to detect whether a positive result is noteworthy (FPRP threshold is 0.2 and prior probability level is 0.25).…”
Section: Methodsmentioning
confidence: 99%
“…A high level of lamin B1 expression predicts poor OS and DFS for cancer patients. 875 Lamin B1 is overexpressed and facilitates cell proliferation and metastasis in HCC, and increased lamin B1 expression indicates a dismal prognosis and immunotherapy response in HCC. 876 Besides, lamin B1 has been proposed as a prognostic senescence biomarker in ccRCC 877 and lung adenocarcinoma.…”
Section: Classification Of Tumor Biomarkersmentioning
confidence: 99%